2018
DOI: 10.1590/1678-4766e2018028
|View full text |Cite
|
Sign up to set email alerts
|

Habitat complexity does not influence prey consumption in an experimental three-level trophic chain

Abstract: Habitat complexity influences species diversity and regulates trophic interactions, mostly by increasing resource partitioning within habitats and providing refuge for prey. The influence of habitat complexity on more than two trophic levels is not well understood, mainly because behavioral modifications of prey and predator may influence the outcome of trophic interactions. Thus, we conducted a two-factor experiment with a three-level trophic chain: a piscivorous fish [Hoplerythrinus unitaeniatus (Spix & … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 59 publications
(88 reference statements)
0
2
0
Order By: Relevance
“…Agostinho et al, 2007). H. unitaeniatus is a voracious piscivore with a high activity level (Granzotti et al, 2018;Lopes et al, 2021), which allows us to assess its predatory behaviour. Moreover, although Gonino et al (2019a) have revealed the lethal effects of SCA at a concentration of 1981.74 mg/L for M. forestii, no information is available on non-lethal effects of sublethal concentrations for either H. unitaeniatus or M. forestii.…”
Section: Studied Species and Housingmentioning
confidence: 99%
See 1 more Smart Citation
“…Agostinho et al, 2007). H. unitaeniatus is a voracious piscivore with a high activity level (Granzotti et al, 2018;Lopes et al, 2021), which allows us to assess its predatory behaviour. Moreover, although Gonino et al (2019a) have revealed the lethal effects of SCA at a concentration of 1981.74 mg/L for M. forestii, no information is available on non-lethal effects of sublethal concentrations for either H. unitaeniatus or M. forestii.…”
Section: Studied Species and Housingmentioning
confidence: 99%
“…2 Mean and standard error of Hoplerythrinus unitaeniatus behavioural traits measured in frequency (%) and duration (minutes) under treatments of fish exposure to sublethal con-centrations of sugarcane ashes (SCA) (0.8 g L −1 of SCA for 24 h) (No SCA, no SCA addition; Prey SCA, only prey exposed to SCA; Predator-Prey SCA, predator and prey exposed to SCA) of pollutants on the behaviour of aquatic organisms is individual-dependent (Blake & Gabor, 2014;Sih et al, 2004). For H. unitaeniatus, previous experimental studies have demonstrated individual differences in the strategy to capture its prey (Granzotti et al, 2018). Individuals within populations can differ in a wide spectrum of traits, including the behavioural ones (Dingemanse et al, Table 2 Analysis of deviance table (type II test) of fixed variables: treatments of fish exposure to sublethal concentrations of SCA (three levels: "no SCA addition", "prey SCA exposition", "predator and prey SCA exposition") and time (three levels: "after 1 h", "after 12 h" and "after 24 h" of co-occurrence between predator and prey) from generalized mixed models on the percentage of prey consumed (i.e.…”
Section: The Effects Of Acute Sca Exposure On the Behaviour Of Predator Fish Speciesmentioning
confidence: 99%